Antibiotic Prescription in Critically Ill Patient in Intensive Care Unit of a Tertiary-Level Hospital of a Lower-Middle Income Country - Pant, Chiranjibi; Rajbhandari, Ajay; Khadka, Anjan; KC, Rajesh; Pal, Anusmriti; Shrestha, Dipesh (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Antibiotic resistance is a major global health concern, particularly in lower-middle income countries. High burden of infections in intensive care units (ICUs) and empirical use of broad- spectrum antibiotics can contribute to the emergence of multidrug- resistant (MDR) organisms. This study aimed to assess the antibiotic prescription pattern in the ICU of a tertiary-level hospital of central Nepal.Methods: A descriptive, cross-sectional study was conducted over the period of 6months analyzing the records of 249 patients admitted to the ICU. All patients aged 14 years or above admitted to the ICU for a minimum of 24 hours were included in the study. Data on patient demographics, diagnosis, antibiotic prescriptions, culture results, and sensitivity patterns were collected and analyzed.Results: Among 249 patients, 142 were male, with a mean age of 63.07±16.84 years. The average length of stay (LOS) in ICU was 8.72±6.99 days. The most common diagnoses were acute exacerbation of chronic obstructive pulmonary disease (19.3%), septic shock (16.1%), and pneumonia (14.9%). Cultures were positive in 96 cases. Respiratory specimens were the most frequent source (74.3%), and Acinetobacter species (49%) was the predominant isolate. Empiric antibiotics were prescribed to 234 (94%) patients, with 85.5% receiving two or more antibiotics.Conclusions: Empirical antibiotic use is highly prevalent with a significant burden of MDR pathogens, notably Acinetobacter species in our setting. Regular surveillance of antibiotic use and resistance patterns, along with ICU-specific antibiotic protocols, are essential to promote rational antimicrobial use and combat rising resistance in Nepalese healthcare settings.